Methanol synthesis from CO2/H2 using Ga2O3-Pd/SiO2 catalysts: Impact of reaction products - Chiavassa, Dante Luis (2008)
The synthesis of CH3OH from CO2/H2 mixtures using Ga2O3–Pd/SiO2 promoted catalysts is strongly affected by the reaction products. At finite conversion, important amounts of water and carbon monoxide are also found in the system and, therefore, a comprehensive evaluation of their impact on the process is particularly relevant. An experimental program was conducted, using a plug-flow, differential reactor and a Berty-type CSTR recycle reactor, for a wide range of temperature (508–538 K), pressure (1–4 MPa), composition (H2/CO2 = 1, 3 and 6) and space velocity, including H2–CO–CO2 and H2–He–CO2 ternary mixtures as well. The deleterious effect of CO is attributed to its strong chemisorptive bonding onto the metal, which hampers the generation and transfer of dissociated hydrogen, Hs, from the Pd crystallites to the Ga2O3; this effect alters both the activity and the selectivity of the catalyst. The detrimental impact of H2O, which is produced in every stoichiometric reaction of the system, is related to its interference on the availability of coordinatively unsaturated sites (cus) on the gallia surface.